-69-3x=71+2x

Simple and best practice solution for -69-3x=71+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -69-3x=71+2x equation:


Simplifying
-69 + -3x = 71 + 2x

Solving
-69 + -3x = 71 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-69 + -3x + -2x = 71 + 2x + -2x

Combine like terms: -3x + -2x = -5x
-69 + -5x = 71 + 2x + -2x

Combine like terms: 2x + -2x = 0
-69 + -5x = 71 + 0
-69 + -5x = 71

Add '69' to each side of the equation.
-69 + 69 + -5x = 71 + 69

Combine like terms: -69 + 69 = 0
0 + -5x = 71 + 69
-5x = 71 + 69

Combine like terms: 71 + 69 = 140
-5x = 140

Divide each side by '-5'.
x = -28

Simplifying
x = -28

See similar equations:

| 7/8=7×1/8 | | -65+4x=61+11x | | -3/13p=-8 | | 4ex=10 | | -36=-10-2x | | 50+15x=110 | | ex=15 | | x+x+43=101 | | 43+(x*x)=101 | | -6x-60=32-10x | | 8y+1-5y=1+2y-7 | | 11x-9=3x+6 | | 43(x-x)=101 | | 8+6=4816 | | 0=2x^3-3x^2+x-1 | | 21+3y-2=12y-11-4y | | -88-4x=38+3x | | 29(2+x)=101 | | H=12+-16t^2 | | 4+25x=15x+28 | | -88-4x=38 | | 29x+x=101 | | x/4=.80 | | 3x+6=-3x-6 | | -4x+32=104 | | 6x-5=7x+7 | | -46=-11-5x | | 5x+8=-20-2x | | 5n^2-25n-2322=0 | | 115=-1x+140 | | 4+4x=-14+x | | 9m^3+m^2=0 |

Equations solver categories